The Communication of a Folklore Linguistics with Different Scientific Disciplines - Сердега, Руслан Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In this article we are talking about new studies in the linguistic industry knowledge. This branch of science is studying the folklore language. Due to the proposed A. T. Khrolenko term, it was called folklore linguistics. In the article we try to describe the communication of folklore linguistics with different scientific and educational disciplines (philology, social science and even natural science), emphasize its interdisciplinary status. The future prospects of our research we see in the preparation of academic publications. This publication will outline the specifics folklore linguistics as a scientific and academic discipline. It will show its relationship with different branches of knowledge.